Pengaruh Lokasi dan Fasilitas Terhadap Keputusan Berkunjung di Pantai Pasir Putih Tampora Kecamatan Banyuglugur Kabupten Situbondo - Andika Eko Prasetio; Zumrotul Fitriyah (Universitas Pamulang, 2023)
Indonesia is a country consisting of land and sea that stretches from Sabang to Merauke and has a very beautiful natural charm and is suitable for tourism. The tourism sector plays an important role in economic growth. This is in the sense that tourism is one of the industrial sectors that plays a role in increasing income in Indonesia. The research method uses quantitative procedures. This study aims to determine the effect of location and facilities on visiting decisions at Pasir Putih Tampora Beach, Banyuglugur District, Situbondo Regency. Collecting samples using non-probability sampling by taking accidental sampling as respondents. There are 98 tourists who have visited tourist objects as accidental sampling respondents. Then the data were analyzed using the PLS (Partial Least Square) procedure. Therefore, this study found that the location and facilities contributed to the decision to visit the Tampora White Sand Beach, Banyuglugur District, Situbondo Regency.